Chloroquine ameliorates carbon tetrachloride-induced acute liver injury in mice via the concomitant inhibition of inflammation and induction of apoptosis. Issue 12 (December 2018) - Dai, Chongshan; Xiao, Xilong; Li, Daowen; Tun, Sun; Wang, Ying; Velkov, Tony; Tang, Shusheng
Abstract This is the first study to investigate the hepatoprotective effect of CQ on acute liver injury caused by carbon tetrachloride (CCl4 ) in a murine model and the underlying molecular mechanisms. Ninety-six mice were randomly divided into the control (n = 8), CQ (n = 8), CCl4 (n = 40), and CCl4 + CQ (n = 40) treatment groups. In the CCl4 group, mice were intraperitoneally (i.p) injected with 0.3% CCl4 (10 mL/kg, dissolved in olive oil); in the CCl4 + CQ group, mice were i.p injected with CQ at 50 mg/kg at 2, 24, and 48 h before CCl4 administration. The mice in the control and CQ groups were administered with an equal vehicle or CQ (50 mg/kg). Mice were killed at 2, 6, 12, 24, 48 h post CCl4 treatment and their livers were harvested for analysis. The results showed that CQ pre-treatment markedly inhibited CCl4 -induced acute liver injury, which was evidenced by decreased serum transaminase, aspartate transaminase and lower histological scores of liver injury. CQ pretreatment downregulated the CCl4 -induced hepatic tissue expression of high-mobility group box 1 (HMGB1) and the levels of serum HMGB1 as well as IL-6 and TNF-α. Furthermore, CQ pre-treatment inhibited autophagy, downregulated NF-kB expression, upregulated p53 expression, increased the ratio of Bax/Bcl-2, and increased the activation of caspase-3 in hepatic tissue. This is the first study to demonstrate that CQ ameliorates CCl4 -induced acute liver injury via the inhibition of HMGB1-mediated inflammatory responses and the stimulation of pro-apoptotic pathways to modulate the apoptotic and inflammatory responses associated with progress of liver damage.